The Effect of Taxpayer Awareness, Understanding’s Knowledge of Taxation on Compliance of Small and Medium Micro Business Taxpayers at Pratama Tax Service Office Cibitung - Agus Subagiyo; Siti Nurbaity; Khikmatul Islah; Rudianto Hermawan; Ahmad Junaidi (Yayasan Ilomata, 2022)
The number of small and micro business taxpayers at the Cibitung Pratama Tax Office from year to year after the increase, but the high increase in the number of taxpayers is not directly proportional to the increase in taxpayer compliance in paying and notifying the tax. The purpose of this research is to recognize the influence of understanding, the description and knowledge of taxpayers on the compliance of small and medium-sized micro business taxpayers at KPP Pratama Cibitung. The population in this research is a small intermediate micro business taxpayer registered at KPP Pratama Cibitung. The procedure for taking illustrations in this research uses accidental sampling, on the contrary, the collection of information through the questionnaire method. The illustrations used in this research are 100 respondents. In this research, hypotheses are tested using multiple linear regression analysis. The results of this research display that understanding, descriptions, and knowledge of taxpayers regarding partial taxation influence the compliance of small and medium-sized micro business taxpayers in the Cibitung Pratama Tax Office.